Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene